Low perforin expression of early differentiated HCV-specific CD8+ T cells limits their hepatotoxic potential - Jo, Juandy; Lohmann, Volker (Journal of hepatology, 2012)
Background & Aims Perforin plays a central role in the immunopathogenesis of different viral infections. However, its role in hepatitis C virus (HCV) infection has not been fully understood. Here, we analyzed two closely related questions: first, is CD8+ T cell-mediated killing of HCV-replicating human hepatoma cells mediated by perforin? Second, if so, do HCV-specific CD8+ T cells obtained from chronically HCV infected patients express and upregulate perforin? Methods Susceptibility of HCV-replicating human hepatoma cells to the cytotoxic pathway was tested in vitro by addition of perforin substitute streptolysin O and granzyme B and by co-culture experiments with a perforin-expressing HCV-specific CD8+ T cell clone in the presence of perforin or caspase inhibitors. HCV-specific CD8+ T cells were obtained and analyzed for perforin expression and differentiation markers ex vivo from 12 chronically infected patients and 12 patients with resolved HCV infection. Results HCV-replicating human hepatoma cells were susceptible to cytotoxic killing in vitro and a dominant role of perforin in HCV-specific CD8+ T cell-mediated cytolysis was observed. However, HCV-specific CD8+ T cells obtained ex vivo from chronically HCV infected patients expressed only low levels of perforin and showed an impaired ability to upregulate perforin. This was tightly linked to the distinct differentiation stage of HCV-specific CD8+ T cell differentiation ex vivo since early and intermediate differentiated HCV-specific CD8+ T cells only showed weak perforin expression in contrast to late differentiated CD8+ T cells that displayed strong perforin expression. Conclusions Our results suggest that perforin plays a dominant role in CD8+ T cell-mediated lysis of HCV-replicating human hepatoma cells but that lysis may be limited in human chronic viral infection by the low perforin expression of early/intermediate differentiated HCV-specific CD8+ T cells.